Foreign vs. domestic listing: An entrepreneurial decision - Ding, Yuan; Nowak, Eric; Zhang, Hua (Journal of Business Venturing, 2010)
In this paper, we use a unique hand-collected dataset to analyze stock listing as an entrepreneurial decision. By comparing mainland Chinese entrepreneurial firms listed in Hong Kong with the same type of firms opting for a domestic listing on the Shenzhen second board market, we argue that the decision to list on a particular stock exchange is a question of entrepreneurial signaling, and often a trade-off between short-term financial considerations and the entrepreneur's pursuit of long-term benefits.